The Effect of Capital Intensity and Leverage on Tax Planning with Transfer Pricing as an Intervening Variable - Vania Putri Sanda Salsabila; Usman Sastradipraja; Wiwi Hartika (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Tax revenue is a major source of state revenue, but tax planning practices by companies remain a challenge in optimizing tax revenue in Indonesia. Companies tend to utilize various strategies, such as capital intensity, leverage, and transfer pricing, to legally reduce their tax burden. This study aims to analyze the effect of capital intensity and leverage on tax planning, with transfer pricing as an intervening variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study employed quantitative methods with a descriptive and associative approach. The sampling technique used purposive sampling with secondary data in the form of the companies' annual financial reports. Data analysis was performed using multiple linear regression analysis, classical assumption tests, t-tests, F-tests, coefficients of determination, and path analysis using SPSS version 27. The results showed that capital intensity and leverage had a significant negative effect on tax planning. Capital intensity and leverage also had a significant positive effect on transfer pricing. Furthermore, transfer pricing was able to mediate the effect of capital intensity and leverage on tax planning. Simultaneously, capital intensity and leverage significantly influence transfer pricing, while capital intensity, leverage, and transfer pricing jointly significantly influence tax planning. This research shows that corporate asset structure and funding policies can influence tax planning practices both directly and through transfer pricing mechanisms.